Expansion of Oil Palm and Changes in the Local EconomicStructure in Kubu Raya Regency - Tiara Sari; Sulaiman; Agustina (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2025)
The expansion of oil palm in Kubu Raya Regency has become a major driver of local economic transformation, significantly impacting the social and economic structure of the community. This study aims to examine how the development of the oil palm industry has changed patterns of income, employment, and economic activities at the village level. The research employs a qualitative method with a socio-ekonomic approach. Data collection was conducted through observation, interviews, and documentation. Data analysis was carried out using data condensation, data display, and drawing conclusions. The results indicate that the growth of the oil palm industry in Kubu Raya Regency has brought substantial changes to the local economy, marked by increased community income, the opening of new employment opportunities, and enhanced economic activities at the village level. However, these advancements have also raised several serious issues, such as agrarian conflicts, shifts in employment structure, social inequality, and environmental damage caused by the conversion of forests and peatlands. Therefore, inclusive, fair, and sustainable management is required so that economic benefits can be enjoyed without sacrificing social welfare or environmental sustainability in the future. Abstrak Ekspansi kelapa sawit di Kabupaten Kubu Raya telah menjadi pendorong utama transformasi ekonomi lokal dengan dampak signifikan terhadap struktur sosial dan ekonomi masyarakat. Penelitian ini bertujuan untuk mengkaji bagaimana perkembangan industri kelapa sawit mengubah pola pendapatan, lapangan kerja, dan aktivitas ekonomi di tingkat desa. Metode penelitian kualiatatif dengan pendekatan ekonomi-politik. Pengumpulan data dilakukan dengan observasi, wawancara dan dokumentasi. Analisis data dilakukan dengan kondensasi data, display data dan menarik Kesimpulan. Hasil penelitian menunjukkan bahwa Perkembangan industri kelapa sawit di Kabupaten Kubu Raya telah membawa perubahan besar pada perekonomian lokal, yang ditandai dengan meningkatnya pendapatan masyarakat, terbukanya lapangan pekerjaan baru, serta meningkatnya aktivitas ekonomi di tingkat desa. Meski demikian, kemajuan ini juga menimbulkan berbagai persoalan serius, seperti sengketa agraria, pergeseran struktur pekerjaan, ketidakmerataan sosial, serta kerusakan lingkungan yang disebabkan oleh alih fungsi hutan dan lahan gambut. Dengan demikian, diperlukan pengelolaan yang bersifat inklusif, adil, dan berkelanjutan agar manfaat ekonomi dapat dirasakan tanpa mengorbankan kesejahteraan sosial maupun kelestarian lingkungan di masa depan.